Psychoneuroendocrine associations with momentary pelvic pain in endometriosis - Stein, Katharina van; Stoffel, Martin; Marshall, Anne; Germeyer, Ariane; Herpertz, Sabine; Grinevich, Valéry; Eckstein, Monika; Ditzen, Beate (International journal of behavioral medicine, 2025)
Endometriosis is a gynecological condition which often causes chronic or recurrent pelvic pain (CPP). The disease can thereby impose a significant burden on affected individuals and their romantic relationships. Existing research highlights the substantial influence of stress, social support, and hormonal factors on pain experience, but data from daily life is scarce.